ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI UNTUK MENENTUKAN HARGAJUAL MENGGUNAKAN METODE FULL COSTING PADA UKM SEBLAK WS - Tulus Pujo Nugroho; Abednego Priyatama; Firdaus Ramadhan (Jurnal Ekonomi dan Manajemen, 2022)
The purpose of this study is to determine the cost of production using the full costing method to determinethe selling price of SMEs Seblak WS. The method used in this study is the calculation of the cost ofproduction using the Full Costing method, namely determining the cost of a product that takes into accountall elements of production costs including raw material costs, direct labor costs, and factory overhead costs,which are fixed or variable. The results of this study are the calculation of the cost of production indetermining the selling price using the SME Seblak WS method with the full costing method. So that theresults of the calculation of the cost of production produce a difference in selling prices according to UKMSeblak WS with the full costing method which affects the selling price and profit earned by UKM SeblakWS